Advance care plans in UK care home residents: a service evaluation using a stepped wedge design. (29th March 2022) - Garden, Gill; Usman, Adeela; Readman, Donna; Storey, Lesley; Wilkinson, Lindsey; Wilson, Graham; Dening, Tom; Gordon, Adam L; Gladman, John R F
Abstract: Introduction: advance care planning (ACP) in care homes has high acceptance, increases the proportion of residents dying in place and reduces hospital admissions in research. We investigated whether ACP had similar outcomes when introduced during real-world service implementation. Methods: a service undertaking ACP in Lincoln, UK care homes was evaluated using routine data. Outcomes were proportion of care homes and residents participating in ACP; characteristics of residents choosing/declining ACP and place of death for those with/without ACP. Hospital admissions were analysed using mixed-effects Poisson regression for number of admissions, and a mixed-effects negative binomial model for number of occupied hospital bed days. Results: About 15/24 (63%) eligible homes supported the service, in which 404/508 (79.5%) participants chose ACP. Residents choosing ACP were older, frailer, more cognitively impaired and malnourished; 384/404 (95%) residents choosing ACP recorded their care home as their preferred place of death: 380/404 (94%) declined cardiopulmonary resuscitation. Among deceased residents, 219/248 (88%) and 33/49 (67%) with and without advance care plan respectively died in their care home (relative risk 1.35, 95% confidence interval [CI] 1.1–1.6, P < 0.001). Hospital admission rates and bed occupancy did not differ after implementation. Discussion: About 79.5% participants chose ACP. Those doing so were more likely to die at home. Many homes were unwilling or unable to support the service. Hospital admissions were not reduced. Further research should consider how to enlist the support of all homes and to explore why hospital admissions were not reduced.